2013
DOI: 10.4274/npa.y6267
|View full text |Cite
|
Sign up to set email alerts
|

Multipl Skleroz Hastalarında Mizaç Karakter Özellikleri ve Aleksitimi Düzeyi

Abstract: Araştırma Makalesi / Research Article 34Ya z›fl ma Ad re si/Cor res pon den ce Ad dress: Dr. Murat Kuloğlu, Fırat Üniversitesi Hastanesi, Ruh Sağlığı ve Hastalıkları Kliniği, Elazığ, Türkiye Gsm: +90 533 413 9 897 E-posta: kuloglum@yahoo.com Ge liş ta ri hi/Re cei ved: 15.08.2011 Ka bul ta ri hi/Ac cep ted: 08.03.2012 © Nö rop si ki yat ri Ar şi vi Der gi si, Ga le nos Ya yı ne vi ta ra f›n dan ba s›l m›fl t›r. / © Arc hi ves of Neu ropsy chi atry, pub lis hed by Ga le nos Pub lis hing. ÖZET Amaç: Bu çalışmada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
1
1
Order By: Relevance
“…Eboni et al [16] (2018) found higher alexithymia scores in MS women patients while Levant et al [21] (2009) found higher alexithymia scores in healthy men. Unlike our study Kuloğlu et al (2013) found no significant difference between alexithymia scores considering gender differences. The reason for this is probably because of the differences of demographic characteristics of the samples.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Eboni et al [16] (2018) found higher alexithymia scores in MS women patients while Levant et al [21] (2009) found higher alexithymia scores in healthy men. Unlike our study Kuloğlu et al (2013) found no significant difference between alexithymia scores considering gender differences. The reason for this is probably because of the differences of demographic characteristics of the samples.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study showed high alexithymia scores with high EDSS scores in MS patients which is in correlation with Chalah and Ayache (2017) who in their systematical review reported similar results. [10] Unlike Chalah and Ayache (2017) Kuloğlu et al [22] (2013) found no significant relationship between EDSS and TAS scores which they explained low EDSS scores of the patients enrolled in their study.…”
Section: Discussionmentioning
confidence: 67%